Review on Applications of System Dynamics Method in Regional Water Demand Prediction - QIN Huanhuan (Renmin Zhujiang, 2022)
Water resources are the most important basic natural resources for the sustainable development of the social economy,the controlling element of the ecological environment,and strategic economic resources.With the growth in population and economic development,regional water consumption is increasing,and the imbalance between the supply and demand of water resources has become the “bottleneck” restricting regional economic development.Water demand prediction is an important basis for the planning,management,and sustainable utilization of regional water resources,which involves complex factors such as economic,hydrological,meteorological,social,engineering,and technological factors as well as the industrial structure and industrial and agricultural development.The system dynamics method based on the feedback control theory has significant advantages in the dynamic change,causal mechanism analysis,quantitative analysis and simulation of a multi-factor coupled complex giant system.It has been widely used in the prediction of regional water demand.The system dynamics model of regional water demand prediction can decompose a complex social water use system into multiple interconnected and mutually constrained subsystems.It can clearly show the dynamic change process of water demand of each water use subsystem and obtain accurate prediction results of water demand.In this paper,firstly,the characteristics of the system dynamics method are briefly introduced.Then,the applications of this method in regional water demand are summarized and analyzed from four aspects,i.e.,domestic water demand,industrial water demand,agricultural water demand,and ecological environment water demand.Furthermore,the limitations and deficiencies of this method are given,and its future development trend is discussed,which includes the expansion of the regional scale and the strengthening of the combination and complementarity with other methods.